Brain electrical response to the auditory stimulus during archery shooting - Ertan, H.; Yagcioglu, S.; Korkusuz, F.; Ungan, P. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Archery can be described as a static sport requiring strength and endurance of the upper body, in particular the shoulder girdle. To get a good record in an archery competition, one requires well-balanced and highly reproducible movements during the shooting. The bowstring is released when audible impetus is received from a device called "clicker". As the fall of the clicker is an acoustic stimulus, it may evoke a sequence of electrical potentials that can be recorded from the scalp of an archer. These auditory responses of the brain, which are called Auditory Evoked Potentials (AEPs), occur at different latencies and with various relations to the auditory stimuli. The present study aims at investigating the long-latency responses to clicker sound during Recurve Archery Shooting to see if they display some specificity compared to conventional AEPs. The subjects were 15 archers (9 males, 6 females), who reported normal hearing, had medical histories free of significant neurological problems, and were not taking medication known to affect brain activity. They performed archery shootings from 18 m that is official competition distance with target face. Their mean age was 22.8 years (range 16 yrs - 31 yrs) and their archery experience and highest FITA scores were 5.8 years (range 2 yrs -14 yrs) and 1120 (range 1050-1313), respectively. Each archer has made 72 shots except for the 2nd and 12th subject (total shots=1070). During archery shooting, continuous EEG was recorded between the right earlobe and vertex (Cz) electrodes using a standard Electro-Cap, and it was stored for off-line analysis. The EEG was then 1-12 Hz band pass filtered. AEPs consisted of 200 ms pre- and 800 ms post-stimulus (fall of the clicker) periods. The average evoked potential of each subject was obtained. The main components of these AEPs were the nega tive wave N1 with a peak latency of 142 ± 42 ms and the positive wave P2 with a peak latency of 212 ± 44 ms. The amplitudes of these waves measured against the average pre-stimulus EEG were as follows: N1: 28 ± 17 uV; P2: 22 ± 21 uV. These quite high amplitude values compared to those of conventional AEPs can be explained by a synchronization which may occur during archery shooting among the components that are known to constitute the N1 wave. Different lobes and regions of the brain can be active during the time of the scalp-recorded N1 and simultaneous involvement of several of these areas may be contributing to the electrical field recorded at scalp in the archery shooting condition.